Assessment of patient satisfaction and associated factors in an outpatient department at Dangila primary hospital, Awi zone, Northwest Ethiopia, 2018. Issue 1 (1st January 2020) - Asres, Abiyot Wolie; Hunegnaw, Woldeamilak Adamu; Ferede, Addisu Gashinet; Denekew, Habtamu Temesgen
ABSTRACT: Various problems were faced by patients in any hospital outpatient department. But, Patients seek quick and convenient services. Patient satisfaction improves clinical outcomes and patient retention and reduces medical malpractices. Efficient and patient-centered health care delivery is of utmost importance. Thus, patient satisfaction is a very effective indicator to measure the success of health outcomes and plays a key role in improving health service quality and early report of new outbreaks (e.g., Covid-19) or other outbreaks (e, g measles, polio). Objective of this study was to assess patient satisfaction and associated factors on outpatient department, Dangila Primary Hospital, Awi zone, Northwest Ethiopia, 2018. Cross sectional study design was conducted from April 1 st  to August 31 st, 2018. A total of 304 respondents were selected using systematic random sampling. Structured questionnaire was used for data collection. EPI Data version 3.1 and SPSS version 20 were used for data entry and analysis, respectively. Multiple logistic regression was employed to describe associated factors and control potential confounders. Of all 304 participants, 175 (57.6%) were males and 129 (42.4%) were females. About 100 (32.9%) were with age range of 30-39 years. Nearly three-fourth of respondents, 233 (76.6%) were dissatisfied with the queue system to see a doctor. Level of patient satisfaction and waiting time in outpatient department was 48.2% and 48 minutes, respectively.  Multivariate logistic regression indicated that satisfaction with courtesy and respect (p=0.013) and satisfaction with confidentiality taken by the examiner during physical examination (p=0.012) were associated factors for patient satisfaction. Patient satisfaction in outpatient department in Dangila primary hospital was lower than regional target. Courtesy and respect and satisfaction with confidentiality taken by the examiner during physical examination were associated factors for patient satisfaction. Outpatient waiting time was less than one hour.